Governmentality and Power Dynamics in Healthcare Practice: A Foucauldian Perspective - Muhammad Syukur; Firdaus W. Suhaeb; Muhammad Ilyas (HealthCare Nursing Journal, 2026)
This article analyzes governmentality and power dynamics in contemporary healthcare practice through a Foucauldian perspective. It argues that healthcare does not operate only through clinical intervention, public policy, and medical expertise, but also through everyday mechanisms that form subjects who monitor, discipline, and manage their own bodies. Using a narrative-critical literature review, this article synthesizes Foucauldian concepts of power/knowledge, discipline, biopower, normalization, and governmentality with critical health studies and selected policy documents on public health, digital health, primary care integration, non-communicable disease screening, SATUSEHAT, and BPJS Kesehatan. The analysis shows that health education functions as a mechanism of behavioral formation; screening programs operate as surveillance technologies that classify risk; electronic medical records and digital platforms produce standardized medical knowledge; and insurance administration shapes access, compliance, and responsibility. These mechanisms are ambivalent: they can expand prevention, continuity of care, and population protection, yet they may also intensify surveillance, stigma, self-blame, data inequality, and unequal access when social determinants are neglected. The article contributes to socio-critical health studies by offering an analytical framework that links bodies, knowledge, policy, technology, markets, and power in healthcare governance.